Sedimentary and structural evolution of the Eastern South Korea Plateau (ESKP), East Sea (Japan Sea). (August 2017) - Horozal, Senay; Kim, Gil-Young; Cukur, Deniz; Bahk, Jang-Jun; Buchs, David; Ryu, Byong-Jae; Lee, Gwang Hoon; Kim, Seong-Pil
Abstract: The East Sea (Japan Sea) is a semi-enclosed back-arc basin that is thought to preserve a significant record of tectonic evolution and paleo-climatic changes of Eastern Asia during the Neogene. We use here 2-D regional multi-channel seismic reflection profiles and borehole data from Expedition 346 of the Integrated Ocean Drilling Program (IODP) to provide new constraints on the geological history of the Eastern South Korea Plateau (ESKP). The ESKP represents a structurally-complex basement high in the southwestern East Sea which formed during rifting of the back-arc basin. Our new observations show that the ESKP is composed of numerous horsts and grabens controlled by NE-trending normal faults. The acoustic basement is blanketed by Oligocene to recent sediments that have preferentially accumulated in topographic lows (up to 1.5 km thick) and have been cored during Expedition 346 at Site U1430 close to the southern margin of the ESKP. Seismic profiles in the ESKP reveal three units separated by regional unconformities. These seismic units closely correspond to IODP lithostratigraphic units defined at Site U1430, where biostratigraphic data can be used to constrain the timing of three main evolutionary stages of the ESKP. Stage 1 was related to rifting in the late Oligocene and middle Miocene, terminated by a regional uplift leading to an erosional phase in the middle Miocene. Stage 2 was associated with subsidence in the middle and late Miocene and uplift and accompanying erosion or non-deposition in the latest late Miocene. Stage 3 (Pliocene to present) recorded overall uniform hemipelagic-pelagic subsidence of the ESKP with short-lived tectonically-induced uplifts in the late middle Miocene and latest Miocene-early Pliocene. The three stages of evolution of the ESKP closely correlate to sedimentary changes since the Oligocene and suggest a direct control of regional/local tectonics on sedimentation patterns in the southwestern East Sea, with secondary influence of regional climatic and paleo-oceanographic processes. Highlights: We document seismic stratigraphy and structure of the Eastern South Korea Plateau. We correlated seismic reflection data with the IODP drilling data. Stratigraphic units define three main stages of tectonic evolution of the ESKP. Three evolutionary stages closely correlate to sedimentary changes at Site U1430. Our results suggest a direct control of tectonics on sedimentation patterns.